Alcohol and Lateral Inhibitory Interactions in Human Vision. (December 2013) - Johnston, Kevin; Timney, Brian
Acute alcohol consumption detrimentally affects many aspects of visual function, but few studies have addressed the neural mechanisms underlying such changes. One candidate mechanism that may be responsible for some alcohol-induced changes in visual function is lateral inhibition. Alcohol has been shown to abolish lateral inhibitory interactions in experimental preparations in which it is applied directly to the retina, but few studies have attempted to link alcohol-induced reductions in lateral inhibitory interactions with psychophysical performance in assessments of visual function dependent on this mechanism. In the present series of studies we addressed this by investigating the effects of alcohol consumption on a perceptual phenomenon mediated in part by lateral inhibition, the Hermann grid illusion. Participants estimated the contrast of the illusory blobs present at the grid intersections using a matching procedure after consumption of a drink containing alcohol or a nonalcoholic drink. The magnitude of the illusion was diminished in the alcohol condition, and this effect was consistent when we parametrically varied the contrast of the grid squares and widths of the grid bars. These data suggest that alcohol reduces lateral inhibitory interactions in human vision.